2016
DOI: 10.1007/164_2016_23
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus and Other Corneal Diseases: Pharmacologic Cross-Linking and Future Therapy

Abstract: The ability to cross-link collagen fibers and use this technique to strengthen the cornea has become of great interest to ophthalmologists in the last decade. For progressive diseases such as keratoconus, collagen cross-linking confers the possibility of halting progression and stabilizing the cornea, a benefit that is not observed with any other current treatment. Collagen cross-linking uses riboflavin combined with ultraviolet A light to induce the formation of bonds between collagen fibrils that strengthen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…Another common method for polymer crosslinking, specifically collagen, involves using riboflavin as a photoreactive group. Riboflavin (vitamin B2) is mainly used in ophthalmic and tissue engineering applications to enhance corneal strength and tailor mechanical properties of collagen constructs (Tirella et al, 2012;Rich et al, 2014;Hsu and Sugar, 2017). Recently, it has also been used for crosslinking GFs, such as EGF, bFGF, and TGF-β1, onto collagen-based biomaterials (Bertolo et al, 2015;Fernandes-Cunha et al, 2017).…”
Section: Light-induced Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common method for polymer crosslinking, specifically collagen, involves using riboflavin as a photoreactive group. Riboflavin (vitamin B2) is mainly used in ophthalmic and tissue engineering applications to enhance corneal strength and tailor mechanical properties of collagen constructs (Tirella et al, 2012;Rich et al, 2014;Hsu and Sugar, 2017). Recently, it has also been used for crosslinking GFs, such as EGF, bFGF, and TGF-β1, onto collagen-based biomaterials (Bertolo et al, 2015;Fernandes-Cunha et al, 2017).…”
Section: Light-induced Immobilizationmentioning
confidence: 99%
“…During exposure to UV light, oxygen species are released from the carboxylic groups of riboflavin, leading to the generation of light-activated riboflavin and single reactive oxygens. These highly reactive molecules then induce the formation of covalent bonds by reacting with the amino acids from the GF and collagen (Rich et al, 2014;Hsu and Sugar, 2017). It has been suggested that possible vulnerable amino acids to photochemical crosslinking using riboflavin include tyrosine, histidine, cysteine and methionine (Rich et al, 2014).…”
Section: Light-induced Immobilizationmentioning
confidence: 99%
“…Corneal cross-linking has already shown promising efficacy on various ectatic diseases, by halting progression and stabilizing the cornea [ 15 ]. This technique also has benefits in infectious keratitis, including keratitis caused by bacteria, fungi, and Acanthamoeba , by blocking corneal melting together with antimicrobial properties [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method exploits the property of riboflavin to generate, under UVA irradiation, reactive oxygen species that further interact with biological assemblies [ 5 ]. The CXL method is also applied for the treatment of other diseases associated with the extracellular matrix involving various veins [ 6 ], degraded dentine [ 7 ], or the eye (pellucid marginal corneal degeneration, post-LASIK ectasia, infectious keratitis, bullous keratopathy) [ 8 , 9 , 10 , 11 ]. Although numerous clinical trials involving patients with KC are dedicated to the analysis of the efficacy and effects of CXL, literature data are scarce on the physicochemical aspects behind this treatment.…”
Section: Introductionmentioning
confidence: 99%